Levantamento e identificação de doenças fúngicas de fruteiras nativas da Mata Atlântica e controle alternativo com guaçatongueira - Bernardi, Caliandra (2024)
Native fruit trees are the treasure of Brazilian biodiversity, and their fruits can be onsumed fresh or used to obtain industrial products, in the food, pharmaceutical or cosmetics range. One of the biggest problems facing native fruit plants is the lack of knowledge of the main diseases that affect the fruits, leaves, flowers, branches and roots of these species during the stages of their development, which does not allow correct control to be carried out. Therefore, the objective of this work was to identify and characterize molecularly and morphologically the pathogens that cause diseases in some native fruit plants of the Myrtaceae family. Plants from the UTFPR Native Fruit Collection Campus Dois Vizinhos were analyzed. From these, fruits, leaves, flowers and branches with disease symptoms were collected, in the four seasons of the year. Subsequently, the collected plant material was taken to the Phytopathology Laboratory on the campus for isolation of microorganisms. After being isolated, some were characterized morphologically and molecularly in order to identify the disease and its causal agents. Finally, alternative in vitro control of some diseases was carried out with guaçatongueira plant extract. It is concluded that the plant extract presents antioxidant and antimicrobial activity against the pathogens evaluated, as well as five new fungal diseases, never reported before in Brazil (4) and Paraná (1), were identified and catalogued.